THE EFFECT OF HEAVY BAG THRUST TRAINING ON THE RESULTS OF PENCAK SILAT FOREHANDS IN TAPAK SUCI ATHLETES - Silvi Aryanti; Wahyu Indra Bayu; Nurpajriwati Nurpajriwati (Universitas Negeri Medan, 2023)
This study aims to determine the effect of heavy bag thrust training on the results of forehand strokes in Banyuasin black rhinoceros martial arts athletes. This study used a sample of 30 students, collecting data using the forward punch test on pecing with a stopwatch measuring instrument. The method used is a quasy experiment with a pretest-posttest one group design. The results of the forehand pretest obtained the highest score of 22 and the lowest score of 12, while the results of the forehand posttest obtained the highest score of 23 and the lowest score of 12. The treatment in this study was pushing exercises using a heavy bag thrust given for 6 weeks with a frequency of 3 times a week. Test the effectiveness using the quasy experimental method with the results of a significant